Parallelization of spherical discontinuous deformation analysis (SDDA) for geotechnical problems based on cloud computing environment - Jiao, Yu-Yong; Wu, ZeYang; Zheng, Fei; Zhao, Qiang; Wang, Long; Huang, Gang-Hai; Tan, Fei (Science China. Technological sciences, 2021)
The computational efficiency of the traditional serial spherical discontinuous deformation analysis (SDDA) program has limited its application in geotechnical engineering problems that need a large number of spheres. The cloud computing technology is used to parallel the SDDA program for the first time in this research. The most computationally intensive portions of the SDDA program, i.e., contact detection and matrix solution, are parallelized with proposed cconfiguration and the computing scale can be up to several tens of thousands of particles. The cloud-based parallelized SDDA program increases its potential in applications of deformation and failure analysis of large-scale and realistic geotechnical engineering problems.